Dissociation of identity following left parietal haematoma – a single case report. (October 2019) - Sreenivasa, Vyjayanthi; Mayur, Prashanth
Objectives: Dissociative identity disorder in relation to brain injury has only rarely been reported in literature. This case report, which illustrates a de novo onset of dissociative identity for the first time in an elderly man who had a left parietal haematoma, adds to this scant literature base and supports an integrative view of bridging the dichotomy between organic and functional to explain complex psychiatric phenomena. Methods: It is a single case report collected through serial semi-structured interviews of the patient and his family over a 12-week period. Results: The patient was an elderly man transiently dissociated into various identities, some of whom seemed to be based upon individuals who had traumatized him in the past. This occurred three weeks after recovery from hemiparesis and delirium following a left parietal haematoma. The dissociations ended after six weeks, which coincided not only with the resolution of the haematoma but also with a faith-healing ritual. A speculative psychobiological formulation was drawn of possible brain origins of dissociation of identity. Conclusions: This report is a compelling account of temporal correlation between dissociation of identity and left parietal haematoma.